Preliminary Findings from Three Models of Motivational Interviewing Training in Jamaica (Mary Ann Liebert, 2020)
Introduction: We assessed satisfaction, fidelity, retention, and implementation considerations across three models of motivational interviewing training in Jamaica to identify a promising model for resource-poor settings. Methods: We conducted t-tests to assess differences in fidelity and examined qualitative data for barriers and facilitators (n=52). Results: Only 50?75% of all models' trainees completed coaching. Model 1 trainees' mean fidelity was 2.83/4.00 compared with Model 3 trainees' at 2.94/4.00 (t=?0.710, confidence interval=?0.427 to 0.207, p=0.483). Key barriers to completion and fidelity were lack of funding and time. Conclusion: We found support for continuing workshop-only trainings; we did not find that higher contact hours produced improved trainee fidelity.